Post-modernism and Post-compulsory Education - Halliday, John (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2001)
This paper examines and elaborates upon the work of two writers, Usher and Edwards who have explored the significance of post-modernism for those involved in the post-compulsory sector of education. They argue that postmodernism signals an increasing interest in this sector of education and a major challenge to the idea of compulsory schooling. In this paper it is argued that postmodernism challenges the very distinction between compulsory and postcompulsory education. It problematises and disturbs a number of entrenched assumptions about education, teaching and learning in interesting ways. The paper concludes with an outline of what formal education might become as a result of such problematisation and disturbance.